Canada 1919: A Nation Shaped by War - Cook, Tim; Granatstein, J.L. (UBC Press, 2020)
With compelling insight, Canada 1919 examines the year following the Great War–a war that was, for Canada, completely unexpected in its magnitude. In the midst of relief that the killing had ended, economic and political tensions were fraught as the survivors attempted to right the country and chart a path into the future. The Canadian Corps had played a significant role in the war and were hailed as the "shock troops" of the British empire. They came home full of both sorrow and pride in their accomplishments, wondering what they would do, and how would they fit in with their families. The military stumbled through massive demobilization. The government struggled to hang on to power, labour seethed, and the threat of Bolshevism emerged. At the same time there were positive changes, and a new Canadian nationalism was forged. This book offers a fresh perspective on the concerns of the time: the treatment of veterans, including nurses and Indigenous soldiers; the place of children; the influenza pandemic; the rising farm lobby; the role of labour; Canada's international standing; and commemoration of the fallen. Canada 1919 exposes the ways in which war shaped Canada–and the ways it did not. – Publisher's description
OCLC: 1135980640
Keywords: 1900-1999; Canada; Canada Conditions sociales 1918-1930; Canada Conditions sociales 20e siècle; Canada Conditions économiques 1918-1945; Canada Economic conditions 1918-1945; Canada Military policy; Canada Politics and government 1914-1945; Canada Politique et gouvernement 1914-1945; Canada Social conditions 1918-1930; Canada Social conditions 20th century; Economic history; Economics; Guerre mondiale; 1914-1918 Aspect social Canada; Guerre mondiale; 1914-1918 Aspect économique Canada; Guerre mondiale; 1914-1918 Canada; Military policy; Ottawa authors; musicians; etc; Politics and government; Social aspects; Social conditions; World War; 1914-1918 Canada; World War; 1914-1918 Economic aspects Canada; World War; 1914-1918 Social aspects Canada

The Law of Work - Doorey, David J. (Emond Publishing, 2020)
[This second edition] presents a comprehensive overview of all aspects of Canadian employment and labour law. Ideal for a non-legal audience, this resource considers the social context in which these laws are made and draws from various disciplines, including economics, management studies, and history. Through short, focused chapters, students will be introduced to the three regimes of work law: common law, regulation, and collective bargaining. Notable legal cases and explanations of key concepts are featured throughout, alongside practical problem-solving exercises and discussion questions that invite readers to apply the law to real-life workplace scenarios. –Publisher's description

Canadian Labour Relations: Law, Policy, and Practice - Doorey, David J.; Braley-Rattai, Alison (Emond Publishing, 2020)
This book offers non-legal students an in-depth exploration of work-related law, policy, and current issues. Topics include the unionization process, collective bargaining, regulation of unions, industrial conflict, collective agreement administration, and notable court decisions. Practical problem-solving exercises and questions are featured throughout in order to help readers apply the law to real-life scenarios. This edition includes updated legislation, mock arbitration and negotiation scenarios, and an entirely new section that explores key policy issues and debates. –Publisher's description

Women and Work: Feminism, Labour, and Social Reproduction - Ferguson, Susan (Between the Lines, 2020)
This edited collection introduces and explores the causes and consequences of precarious employment in Canada and across the world. After contextualizing employment precarity and its root causes, the authors illustrate how precarious employment is created amongst different populations and describe the accompanying social impacts on racialized immigrant women, those in the non-profit sector, temporary foreign workers and the children of Filipino immigrants. –Publisher's description.

The Canadian Precariat: Part-Time Faculty and the Higher-Education System - Gagné, Ann (2020)
This collection includes reflections about the precariousness of academic employment for non-tenured professionals across Canada. It includes articles from those who have taught in post-secondary education across Canada, as well as as from those some who have experienced precarity as student and union organizers. It also includes voices of students working and teaching in the higher education system. The texts are both in the form of critical engagement with the academic discourse and research as well as reflective memoirs on experiences of educational precarity from numerous social locations. They highlight precarity at all levels of employment in the Canadian higher education system and offer suggestions on how to improve this long-standing and damaging reality affecting tens of thousands of the precariously employed. –Publisher's description. Contents: Introduction / Ann Gagné – Manufactured Precarity: Some Solutions to Help Mitigate the Impacts of Precarious Employment of Canadian Sessional Instructors / Amber Diaz – The Tensions of Tenure and Allyship: On Becoming, Speaking, and Listening / Veronica J. Austen – Reflections of Precarity from a Student and Student Representative / Gayle McFadden – Immigrant Precarity in the Academe: The Quebec Version / Cristina Artenie – Towards Best Practices in Canadian Higher Education: A Precarious Memoir in Miniature / Ann Gagné.
OCLC: 1192562186

The Subjectivities and Politics of Occupational Risk: Mines, Farms and Auto Factories - Hall, Alan (Routledge, 2020)
The Subjectivities and Politics of Occupational Risk links restructuring in three industries to shifts in risk subjectivities and politics, both within workplaces and within the safety management and regulative spheres, often leading to conflict and changes in law, political discourses and management approaches. The state and corporate governance emphasis on worker participation and worker rights, internal responsibility, and self-regulative technologies are understood as corporate and state efforts to reconstruct control and responsibility for Occupational Health and Safety (OHS) risks within the context of a globalized neoliberal economy. Part 1 presents a conceptual framework for understanding the subjective bases of worker responses to health and safety hazards using Bourdieu’s concept of habitus and the sociology of risk concepts of trust and uncertainty. Part 2 demonstrates the restructuring arguments using three different industry case studies of multiple mines, farms and auto parts plants. The final chapter draws out the implications of the evidence and theory for social change and presents several recommendations for a more worker-centred politics of health and safety.The book will appeal to social scientists interested in health and safety, work, employment relations and labour law, as well as worker advocates and activists. –Publisher's description. Contents: 1. Introduction and Research MethodsPart 1: Risk Subjectivities and Practices2. Identifying Hazards and Judging Risk3. Taking Risks or Taking a Stand: Interests, Power and IdentityPart 2: Case Studies of Health and Safety in Hard Rock Mining, Family Farming and Auto Parts Manufacturing 4. Transforming the Mining Labour Process: Transforming Risk and its Social Construction5. Reconstructing Miner Consent: Management Objectives and Strategies6. The Transformation and Fragmentation of Canadian Agriculture7. Health and Safety in Farming8. The Transformation of Production and Health and Safety in Auto Parts Manufacturing.9. Participation and Control in a Non-Union Auto Parts Firm10. Conclusion and Implications for Change.

The Canadian Labour Movement: A Short History - Heron, Craig; Smith, Charles W. (Lorimer, 2020)
In The Canadian Labour Movement, historian Craig Heron and political scientist Charles Smith tell the story of Canada's workers from the midnineteenth century through to today, painting a vivid picture of key developments, such as the birth of craft unionism, the breakthroughs of the fifties and sixties, and the setbacks of the early twenty-first century. The fourth edition of this book has been completely updated with a substantial new chapter that covers the period from the great recession of 2008 through to 2020. In this chapter, Smith describes the fallout of the financial crisis, how Stephen Harper's government restricted labour rights, the rise of the "gig economy" and precarious work, and the continued de-industrialization in the private sector. These pressures contributed to fracturing the movement, as when Unifor, the largest private sector union, split from the Canadian Labour Congress, the established "house of labour." Through it all, rank-and-file union members have fought for better conditions for all workers, including through campaigns like the fight for a $15 minimum wage. –Publisher's description

Work, Industry, and Canadian Society - Krahn, Harvey; Hughes, Karen; Lowe, Graham S. (Top Hat, 2020)
Work, Industry, and Canadian Society provides a sociological introduction to the history, nature, organization, and management of work in Canada. The eighth edition expands and adds new coverage on the biggest work challenges faced now and in the future, such as Canada’s aging and increasingly diverse workforce, the work experiences of Canada’s Indigenous peoples, the rise of the app-based “gig” economy, and how technology will continue to impact future jobs and work organization. The new edition continues to incorporate recent empirical findings, review new and ongoing theoretical and policy debates, and provide a more international perspective. As the world of work continues to change rapidly, all trends and statistics have been updated. These authors are well regarded for their teaching and research, and their years of experience are evident in this comprehensive volume on the past, present, and future of work in Canada. –Publisher's description. Contents: Historical perspectives on work – Contemporary debates and issues – Canadian employment trends – Good jobs, bad jobs, no jobs – Labour markets: opportunities and inequality – Gender and paid employment – Household, family, and caring work – Organizing and managing work – In search of new managerial paradigms – Conflict and control in workplace – Unions and industrial relations – Alternative approaches to organizing work – Work values and work orientations – Job satisfaction, alienation, and work-related stress.

Take the Plant, Save the Planet - Leah, Tony; Panitch, Leo; McQuaig, Linda; Gindin, Sam; Keetch, Rebecca; Wells, Jennifer; Christianson, Russ (Socialist Project, 2020)
On November 26, 2018, General Motors announced a number of plant closures in North America, the largest of which was in Oshawa, Ontario. The Oshawa facility, once the largest auto complex on the continent, was to end all its assembly operations by the end of 2019. ...This pamphlet provides background material on Oshawa and joins Green Jobs Oshawa in encouraging workers elsewhere to prepare now for the threats to their jobs and productive capacity that will inevitably come. –From introduction

Closing Sysco: Industrial Decline in Atlantic Canada's Steel City - MacKinnon, Lachlan (University of Toronto Press, 2020)
This book is a history of deindustrialization and working-class resistance in the Cape Breton steel industry between 1945 and 2001. The Sydney Steel Works is at the heart of this study - having existed in tandem with Cape Breton's larger coal operations since the early twentieth century. Chapters explore the multi-faceted nature of deindustrialization, the internal politics of the steelworkers' union, successful efforts to nationalize the mill in 1967, the years in transition under public ownership, and confrontations over health, safety, and environmental degradation in the 1990s and 2000s. The book moves beyond the moment of closure to trace the cultural, historical, and political ramifications of deindustrialization as they continue to play out in post-industrial Cape Breton Island. This represents a significant intervention into the international literature on deindustrialization, pushing scholarship beyond the bounds of political economy and cultural change to begin tackling issues of bodily health, environment, and historical memory in post-industrial places. – Publisher's description
OCLC: 1090428366
Keywords: 1900-1999; Acier Industrie et commerce Nouvelle-Écosse Sydney Histoire 20e siècle; Acier Industrie et commerce Nouvelle-Écosse Sydney Personnel Conditions sociales 20e siècle; Deindustrialization; Deindustrialization Nova Scotia Sydney History 20th century; Deindustrialization Social aspects; Deindustrialization Social aspects Nova Scotia Sydney; Désindustrialisation Aspect social Nouvelle-Écosse Sydney; Désindustrialisation Nouvelle-Écosse Sydney Histoire 20e siècle; History; Nova Scotia Sydney; Plant shutdowns; Plant shutdowns Nova Scotia Sydney History 20th century; Social conditions; Steel industry and trade; Steel industry and trade Nova Scotia Sydney Employees Social conditions 20th century; Steel industry and trade Nova Scotia Sydney History 20th century; Sydney (N.-É.) Conditions sociales 20e siècle; Sydney (N.S.) Social conditions 20th century; Sydney Steel Corporation; Usines Fermeture Nouvelle-Écosse Sydney Histoire 20e siècle

The Violence of Work: New Essays in Canadian and US Labour History - Milloy, Jeremy; Sangster, Joan (2020)
From mining to sex work and from the classroom to the docks, violence has always been a part of work. This collection of essays highlights the many different forms and expressions of violence that have arisen under capitalism in the last two hundred years, as well as how historians of working-class life and labour have understood violence. The editors draw together diverse case studies, integrating analysis of class, age, gender, sexuality, and race into the scholarship. Essays span the United States and Canadian border, exploring gender violence, sexual harassment, the violent kidnapping of union organizers, the violence of inadequate health and safety protections, the culture of violence in state institutions, the mythology of working-class violence, and the changing nature of violence in extractive industries. The Violence of Work theorizes and historicizes violence as an integral part of working life, making it possible to understand the full scope and causes of workplace violence over time. –Publisher's description, Contents: Introduction: Accounting for violence / Jeremy Milloy – The perils of sex work in Montreal: seeking security and justice in the face of violence, 1810-1842 / Mary Anne Poutanen – The rules of discipline: workers and the culture of violence in progressive-era reform schools / James Schmidt – The "new solution": anti-labour kidnapping, D.B. McKay, and the legacy of the second Seminole War / Chad Pearson – Billy Gohl: labour, violence, and myth in the early twentieth-century Pacific Northwest / Aaron Goings – Slow violence and hidden injuries: the work of strip mining in the American west / Ryan Driskell Tate – The murder of Lori Dupont : violence, harassment, and occupational health and safety in Ontarion / Sarah Jessup – "By the nuimbers" : workers' compensation and the (further) conventionalization of workplace violence / Robert Storey – Gender violence in the hospitality industry: panic buttons, pants, and protest / Emily E. LB. Twarog.
OCLC: 1252731475

À l'avant garde du progrès: I'institut professionnel de la fonction publique du Canada 1920-2020 - Russell, Jason (Between the Lines, 2020)
Le 6 février 1920, un petit groupe d’employés de la fonction publique se réunit pour la première fois afin de former une association professionnelle. Un siècle plus tard, l’Institut professionnel de la fonction publique du Canada (IPFPC) est un agent négociateur représentant près de 60 000 travailleurs du secteur public dont les efforts pour le bien collectif améliorent la vie de chaque Canadien. Publié à l’occasion du 100e anniversaire de fondation de l’IPFPC, À l’avant-garde du progrès dresse le portrait complet de son évolution, de 1920 à aujourd’hui, et lève le voile sur un pan souvent négligé de l’histoire syndicale nord-américaine. L’auteur, Jason Russell, s’appuie sur une abondante collection de sources, dont des documents d’archives et des témoignages de dizaines de membres actuels et passés de l’IPFPC. Marquée par des réussites et semée d’embûches, l’histoire est complexe et racontée avec clarté et modération. Après des décennies de changements démographiques et générationnels, de booms et de crises économiques et de bouleversements politiques, les membres de l’IPFPC entament les cent prochaines années guidés par la même mission importante que celle qui les a inspirés jusqu’à présent : militer pour une justice sociale et économique pour le bien de tous les Canadiens et Canadiennes. –Résumé de l'éditeur
OCLC: 1227102677

Leading Progress: The Professional Institute of the Public Service of Canada, 1920-2020 - Russell, Jason (Between the Lines, 2020)
On February 6, 1920, a small group of public service employees met for the first time to form a professional association. A century later, the Professional Institute of the Public Service Canada (PIPSC) is a bargaining agent representing close to 60,000 public sector workers, whose collective efforts for the public good have touched the lives of every Canadian. Published on the centennial of PIPSC’s founding, Leading Progress is the definitive account of its evolution from then to now—and a rare glimpse into an under-studied corner of North American labour history. Researcher Dr. Jason Russell draws on a rich collection of sources, including archival material and oral history interviews with dozens of current and past PIPSC members. The story that unfolds is a complex one, filled with success and struggle, told with clarity and even-handedness. After decades of demographic and generational shifts, economic booms and busts, and political sea change, PIPSC looks toward its next hundred years with its mission as strong as ever: to advocate for social and economic justice that benefits all Canadians. –Publisher's description
OCLC: 1142100040

Inequality in Canada: The History and Politics of an Idea - Sager, Eric W. (McGill-Queen's University Press, 2020)
Economic inequality is one of the great issues of our era. But what is inequality? Eric Sager argues that inequality is more than the distribution of income and wealth. Inequality is the idea that there are wide gaps between rich and poor, that the gaps are both an economic problem and a social injustice, and that the problem can be either eliminated or reduced. This idea arose in a transatlantic world, in the long evolution of political economy in Britain and the United States from classical economics to the emerging welfare economics of the twentieth century. Within this transatlantic frame inequality took a distinct form in Canada. It appeared among radical reformers and republicans in the 1830s. It arose in a critique of wealth among Protestant thinkers and their moral imperatives. The idea appeared among labour radicals and reformers who interpreted the conflict between capital and labour as a problem of distribution. For social gospelers inequality was a simplifying frame that made sense of an alien modernity of industry, urbanism, and class conflict. A tradition of idealist thought persisted in the twentieth century, sustaining the idea of inequality despite deep silences among Canadian economists. The idea appeared forcefully in social Catholicism in Quebec, and then waned in the political and intellectual justifications of the social security state. In the new era of inequality in our century, a political solution may rest upon the recovery of an older ethical idealism and in a historically-informed egalitarian politics."– Publisher's description
OCLC: 1193028647
Keywords: Canada; Classes sociales Canada; Equality; Equality Canada History; Equality Political aspects Canada History; History; Social classes; Social classes Canada; Égalité (Sociologie) Aspect politique Canada Histoire; Égalité (Sociologie) Canada Histoire

Chicken Girl - Smith, Heather (Penguin Random House Canada, 2020)
Poppy used to be an optimist. But after a photo of her dressed as Rosie the Riveter is mocked online, she's having trouble seeing the good in the world. As a result, Poppy trades her beloved vintage clothes for a feathered chicken costume and accepts a job as an anonymous sign waver outside a restaurant. There, Poppy meets six-year-old girl Miracle, who helps Poppy see beyond her own pain, opening her eyes to the people around her: Cam, her twin brother, who is adjusting to life as an openly gay teen; Buck, a charming photographer with a cute British accent and a not-so-cute mean-streak; and Lewis a teen caring for an ailing parent, while struggling to reach the final stages of his gender transition. As the summer unfolds, Poppy stops glorifying the past and starts focusing on the present. But just as she comes to terms with the fact that there is good and bad in everyone, she is tested by a deep betrayal. – Publisher's description
OCLC: 1112907005

How to Pronounce Knife: Stories - Thammavongsa, Souvankham (Penguin Random House Canada, 2020)
Named one of Time's Must-Read Books of 2020, and featuring stories that have appeared in Harper's, Granta, The Atlantic, and The Paris Review, this revelatory book of fiction from O. Henry Award winner Souvankham Thammavongsa establishes her as an essential new voice in Canadian and world literature. Told with compassion and wry humour, these stories honour characters struggling to find their bearings far from home, even as they do the necessary "grunt work of the world." A young man painting nails at the local salon. A woman plucking feathers at a chicken processing plant. A father who packs furniture to move into homes he'll never afford. A housewife learning English from daytime soap operas. In her stunning Giller Prize-winning debut book of fiction, Souvankham Thammavongsa focuses on characters struggling to make a living, illuminating their hopes, disappointments, love affairs, acts of defiance, and above all their pursuit of a place to make their own. In spare, intimate prose charged with emotional power and a sly wit, she paints an indelible portrait of watchful children, wounded men, and restless women caught between cultures, languages, and values. As one of Thammavongsa's characters says, "All we wanted was to live." And in these stories, they do—brightly, ferociously, unforgettably. A daughter becomes an unwilling accomplice in her mother's growing infatuation with country singer Randy Travis. A former boxer finds a chance at redemption while working at his sister's nail salon. A school bus driver must grapple with how much he's willing to give up in order to belong. And in the title story, a young girl's unconditional love for her father transcends language. Tender, uncompromising, and fiercely alive, How to Pronounce Knife establishes Souvankham Thammavongsa as one of the most important voices of her generation. –Publisher's description
OCLC: 1153264906
Keywords: Audiobooks; Downloadable audio books; Livres audio; Nouvelles canadiennes; Short stories Women authors; Short stories; Canadian; Écrits de femmes

Closing the Enforcement Gap: Improving Employment Standards Protections for People in Precarious Jobs - Vosko, Leah F.; Closing the Enforcement Gap Research Group; Grundy, John; Akkayamak, Guliz; Noack, Andrea M.; Casey, Rebecca; Hoe, Alice; Hall, Alan; Tucker, Eric; Condratto, Shelley; Mirchandani, Kiran; Soni-Sinha, Urvashi; et al. (University of Toronto Press, 2020)
The nature of employment is changing: low wage jobs are increasingly common, fewer workers belong to unions, and workplaces are being transformed through the growth of contracting-out, franchising, and extended supply chains. Closing the Enforcement Gap offers a comprehensive analysis of the enforcement of employment standards in Ontario. Adopting mixed methods, this work includes qualitative research involving in-depth interviews with workers, community advocates, and enforcement officials; extensive archival research excavating decades of ministerial records; and analysis of a previously untapped source of administrative data collected by Ontario’s Ministry of Labour. The authors reveal and trace the roots of a deepening "enforcement gap" that pervades nearly all aspects of the regime, demonstrating that the province’s Employment Standards Act (ESA) fails too many workers who rely on the floor of minimum conditions it was devised to provide. Arguably, there is nothing inevitable about the enforcement gap in Ontario or for that matter elsewhere. Through contributions from leading employment standards enforcement scholars in the US, the UK, and Australia, as well as Quebec, Closing the Enforcement Gap surveys innovative enforcement models that are emerging in a variety of jurisdictions and sets out a bold vision for strengthening employment standards enforcement. – Publisher's description.
OCLC: 1121454404

Histoire du taxi à Montréal : des taxis jaunes à UberX - Warren, Jean-Philippe (Boréal, 2020)
Comme toutes les grandes villes occidentales, Montréal fourmille de taxis qui parcourent les rues, font la navette entre l'aéroport et le centre-ville, attendent près des stations de métro, des hôpitaux et des grands hôtels. Trains, tramways, autobus, métros et vélos de Montréal ont eu droit à leur histoire, mais pas les taxis. Le monde du taxi est pourtant un sujet riche et complexe, un carrefour où se rencontrent plusieurs spécialisations de l'histoire : urbaine, politique, économique, sans oublier le travail et l'immigration. Depuis sa voiture, le chauffeur ou la chauffeuse est témoin des rapports tendus entre le travailleur et l'État, la ville et les citoyens, les quartiers excentrés et le centre-ville, le peuple et les élites. Il est aussi témoin des luttes entre la majorité francophone et les minorités culturelles, des mutations technologiques et de l'essor du transport en commun. Le monde du taxi, c'est aussi et surtout des travailleurs qui forment une catégorie sociale unique et qui pratiquent un métier rempli de paradoxes. Au fil de son enquête, faite de recherches sur l'industrie et d'entretiens avec ses acteurs, Jean-Philippe Warren en est venu à la conclusion que le chauffeur de taxi est la dernière incarnation du cowboy : libre de ses mouvements, de son emploi du temps, mais prisonnier de quantité de facteurs. Il peut arrêter de travailler quand il veut et travaille sans cesse. Il a toujours de l'argent dans ses poches, mais est pauvre. Il veut que l'État intervienne pour le protéger, mais exècre les régulations. Il pratique un métier monotone, mais rempli d'imprévus. Il est à la fois entouré de monde et seul. S'ajoutant à la diversité ethnique des membres de la profession, ces paradoxes créent une sous-culture absolument fascinante où se jouent des luttes de pouvoir économique et de contrôle territorial. Une sous-culture tout aussi difficile à intégrer qu'à quitter. En utilisant les ressources combinées de l'histoire et des sciences sociales, en mêlant l'examen des archives et l'enquête de terrain, cette première histoire du taxi à Montréal débouche sur un portrait inédit de la ville. Elle se veut aussi une contribution à la compréhension d'un monde qui cultive les extrêmes et qui, s'il veut se transformer pour le mieux, pour le bien-être de ses travailleurs, de leurs familles et des usagers, doit s'appuyer sur des données tangibles et une histoire critique. –Publisher's description
https://express.editionsboreal.qc.ca/articles/jean-philippe-warren-histoire-du-taxi-a-montreal/?slug=essais-et-documents
Keywords: History; Québec Montréal; Taxicabs; Taxicabs Québec (Province) Montréal History; Taxis Québec (Province) Montréal Histoire

Canadian Political Economy - Whiteside, Heather (University of Toronto Press, 2020)
In Canadian Political Economy, experts from a number of disciplinary backgrounds come together to explore Canada's empirical political economy and the field's contributions to theory and debate. Considering both historical and contemporary approaches to CPE, the contributors pay particular attention to key actors and institutions, as well as developments in Canadian political-economic policies and practices, explored through themes of changes, crises, and conflicts in CPE. Offering up-to-date interpretations, analyses, and descriptions, Canadian Political Economy is accessibly written and suitable for students and scholars. In 17 chapters, the book's topics include theory, history, inequality, work, free trade and fair trade, co-operatives, banking and finance, the environment, Indigeneity, and the gendered politics of political economy. Linking longstanding debates with current developments, this volume represents both a state-of-the-discipline and a state-of-the-art contribution to scholarship. – Publisher's description
OCLC: 1146581412
Keywords: 2000-2099; Canada; Canada Conditions économiques 21e siècle; Canada Economic conditions 21st century; Canada Politics and government 21st century; Canada Politique et gouvernement 21e siècle; Economic history; Economics; Economics Canada; Politics and government; Économie politique Canada